2018
DOI: 10.1186/s12964-018-0221-6
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of adipocyte-derived lipids and enhanced intracellular trafficking of fatty acids contribute to breast cancer progression

Abstract: BackgroundTo determine whether adipocyte-derived lipids could be transferred into breast cancer cells and investigate the underlying mechanisms of subsequent lipolysis and fatty acid trafficking in breast cancer cells.MethodsA Transwell co-culture system was used in which human breast cancer cells were cultured in the absence or presence of differentiated murine 3 T3-L1 adipocytes. Migration/invasion and proliferation abilities were compared between breast cancer cells that were cultivated alone and those co-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 44 publications
2
49
0
Order By: Relevance
“…Intriguingly, breast cancer cells strongly overexpressed levels of ATGL, BDH1, HMGCL and HMGCS2, but decreased the level of PDH. This suggests that breast cancer cells mainly depended on the energy supply via oxidation of fatty acids and ketones instead of pyruvate and is consistent with other research [49]. Taken together, the data indicate that breast cancer cells, acting as metabolic parasites, constantly seized energy and biomass from local adipocytes to fuel tumour growth and metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…Intriguingly, breast cancer cells strongly overexpressed levels of ATGL, BDH1, HMGCL and HMGCS2, but decreased the level of PDH. This suggests that breast cancer cells mainly depended on the energy supply via oxidation of fatty acids and ketones instead of pyruvate and is consistent with other research [49]. Taken together, the data indicate that breast cancer cells, acting as metabolic parasites, constantly seized energy and biomass from local adipocytes to fuel tumour growth and metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, our results indicated that FABP5 mRNA is highly expressed in adipocytes that were co-cultured with breast cancer cells [66]. FABP5 has also been shown to be overexpressed at the invasive front of the breast tumor and linked to poor survival [86, 87]. Similarly, Wang and colleagues described a novel mechanism in which FFAs were released by adipocytes after lipolysis induced by tumor secretions and were transferred into tumor cells to enhance FFA β-oxidation [3], in which FFA transformation maybe attributed to FABP5 high expression [86].…”
Section: The Metabolic Reprogramming Of Caas Drives Cancer Progressionmentioning
confidence: 99%
“…cancer cell membrane and cellular organelle constitution (28,29) ; (b) release of endocrine hormones, growth factors, adipokines, and adipocytokines (refs. 30-44 and Table 1); (c) metabolic reprogramming in cancer cells (2, 3); (d) protease production necessary for cancer invasion (45,46); and (e) recruitment of nonadipocyte stromal cells such as inflammatory cells and vascular cells (47,48).…”
Section: Cancer-associated Adipocytesmentioning
confidence: 99%